Evaluation of Neutralizing Antibodies Against Highly Pathogenic Coronaviruses: A Detailed Protocol for a Rapid Evaluation of Neutralizing Antibodies Using Vesicular Stomatitis Virus Pseudovirus-Based Assay - Almahboub, Sarah A.; Algaissi, Abdullah; Alfaleh, Mohamed A.; ElAssouli, M-Zaki; Hashem, Anwar M. (Frontiers in Microbiology, 2020)
Emerging highly pathogenic human coronaviruses (CoVs) represent a serious ongoing threat to the public health worldwide. The spike (S) proteins of CoVs are surface glycoproteins that facilitate viral entry into host cells via attachment to their respective cellular receptors. The S protein is believed to be a major immunogenic component of CoVs and a target for neutralizing antibodies (nAbs) and most candidate vaccines. Development of a safe and convenient assay is thus urgently needed to determine the prevalence of CoVs nAbs in the population, to study immune response in infected individuals, and to aid in vaccines and viral entry inhibitors evaluation. While live virus-based neutralization assays are used as gold standard serological methods to detect and measure nAbs, handling of highly pathogenic live CoVs requires strict bio-containment conditions in biosafety level-3 (BSL-3) laboratories. On the other hand, use of replication-incompetent pseudoviruses bearing CoVs S proteins could represent a safe and useful method to detect nAbs in serum samples under biosafety level-2 (BSL-2) conditions. Here, we describe a detailed protocol of a safe and convenient assay to generate vesicular stomatitis virus (VSV)-based pseudoviruses to evaluate and measure nAbs against highly pathogenic CoVs. The protocol covers methods to produce VSV pseudovirus bearing the S protein of the Middle East respiratory syndrome-CoV (MERS-CoV) and the severe acute respiratory syndrome-CoV-2 (SARS-CoV-2), pseudovirus titration, and pseudovirus neutralizing assay. Such assay could be adapted by different laboratories and researchers working on highly pathogenic CoVs without the need to handle live viruses in BSL-3 environment.